Radical annulation using a radical reagent as a two-carbon unit. Issue 47 (16th November 2022) - Tang, Boxiao; Liu, Yilin; Lian, Yan; Liu, Hongxin
Abstract : We have highlighted the representative processes reported in the past decade for radical annulation using a radical reagent as a two-carbon unit, including [2 + 2 + 2], [3 + 2], [4 + 2], and [5 + 2] modes, with an emphasis on their reaction mechanisms. Abstract : Radical annulation has emerged as one of the most efficient and straightforward methods for synthesizing cyclic/polycyclic compounds as the core structures can be constructed through a single procedure comprising multiple bond-forming steps. Particularly, radical annulation using a radical reagent as a cyclization partner and two-carbon unit greatly expands the diversity of cyclic skeletons and the functionality of radical reagents. We herein have highlighted the representative processes reported in the past decade for radical annulation using a radical reagent as a two-carbon unit, including [2 + 2 + 2], [3 + 2], [4 + 2], and [5 + 2] modes, with an emphasis on their reaction mechanisms. These studies not only pave the way toward annulation but also provide insight into the exploration of a new reaction mode for radical chemistry.